Cognitive style, graphicacy skills of CXC geography students: Occasional papers - Rohlehr, Betty Ann (My University, 1988)
This study examined the extent to which the geography curriculum of the school determines the performance of graphicacy skills of Caribbean Examinations Council (CXC) Basic and General Proficiency students who vary in cognitive style. The sample consisted of Form 5 students of five- and seven-year schools in Trinidad. The performance of these skills was evaluated by using a Criterion Measure of multiple choice items for graphicacy skills relevant to the CXC geography syllabus. Independent variables of curriculum structure, cognitive style, gender, and proficiency level were related to the dependent variable—graphicacy skills. Analysis of results indicated that there was a significant relationship between field dependence-independence and achievement, after exposure to strategies that correspond to the cognitive style of the individual. The study confirmed that cognitive style is related to performance in graphicacy skills. Field independence performed better than field dependents in graphicacy skills, and there is no significant gender difference in cognitive style. However, field independent males performed better than field dependent males.
UWI. St. Augustine
Keywords: secondary school students; cognitive style; graphicacy skills